The practice of teacher mentoring in Singapore secondary schools - Ho, Shoo Mei. (2008)
This is an exploratory study of teacher mentors’ perceptions of teacher mentoring practice in Singapore secondary schools. It aims to explore the following: (I) the practice of aspects which teacher mentors have acquired from a formal teacher mentoring course; (ii) the practice of aspects which teacher mentors have acquired from other learning sources.